Analisis Faktor-Faktor yang Mempengaruhi Dividend Payout Ratio Pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2008-2010 - G. Gunawan; Dina Febriana (Jurnal Ilmu Manajemen & Ekonomika, 2014)
This research was written in order to find out the relation between cash ratio, debt to equity ratio, firm size and growth to a dividend payout ratio of the manufacturing industry. The samples consisted of 20 manufacturing companies from 2008 through 2010 and still listed on IDX. Research sample using purposive sampling of companies for the period ended 2008 - 2010 analyzed by using the two tail linear regression methodology. The analysis technique used here is multiple regression with the least square difference and hypothesis test using t-statistic to examine partial regression coefficient and F-statistic to examine the mean of mutual effect with level of significance 5%. The result showed that the factors that affect significantly to the dividend payout ratio were a debt to equity ratio and growth. The other factors such as cash ratio and firm size had no significant relations. But the other result of this research showed that cash ratio, debt to equity ratio, firm size and growth were simultaneously had a significant effect on dividend payout ratio.